The Influence of the Environment on Organizational Innovation in Service Companies in Peru - Tsuja, Peter Yamakawa; Ostos, Jhony Lionel (Review of Business Management, 2013)
Several authors consider the environment variable to be an influential element on the innovation variable, but they do not provide further insight of the dimensions of these variables. This study, applied to a sample of service companies, includes dimensions of environment (uncertainty and complexity) and dimensions of innovation (technical and administrative), as well as organizational characteristics as a moderating variable in this relationship between environment and innovation. The results indicate that an uncertain environment promotes only technical innovation, while a complex environment promotes both administrative and technical innovation. It was also found that organizational characteristics partially moderate the relationship between the two variables.